FACTORS INFLUENCING THE INCREASE IN ANTEPARTUM HEMORRHAGE AMONG PREGNANT WOMEN ATTENDING ANTENATAL CLINICS AT EKITI STATE UNIVERSITY TEACHING HOSPITAL, EKITI STATE - Dr. Olabisi Olayinka AWE; Ifeoluwa Adeife OMOTOSHO; Oluwatimilehin Ayodotun AWE (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2026)
Antepartum hemorrhage is defined as vaginal bleeding that occurs after 20 weeks of gestation but before the onset of labor. It remains a significant cause of maternal and fetal morbidity and mortality, necessitating an understanding of its prevalence, risk factors, and contributing factors. This study aimed to determine the factors influencing the increase in antepartum hemorrhage among pregnant women attending antenatal clinics at Ekiti State University Teaching Hospital, Ekiti State. The study employed a simple random sampling technique, with data collected using a self-developed, semi-structured questionnaire containing 43 items. A Total of 74 respondents participated, achieving a valid return rate of 100 percent. The data was analyzed using Statistical Package for Social Sciences (SPSS) version 28 and Microsoft Office Excel version 2016, employing descriptive statistics such as frequencies and percentages. The findings revealed that 13.5 percent of the respondents had experienced antepartum hemorrhage, with varying frequencies of occurrence. Identified risk factors included high parity (27.0 percent strongly agreed, 51.4 percent agreed), pregnancy complications (47.3 percent strongly agreed, 41.9 percent agreed), and a history of uterine surgery (32.4 percent strongly agreed, 39.2 percent agreed). Additionally, factors such as advanced maternal age (41.9 percent strongly agreed, 45.9 percent agreed) and multiple pregnancies (14.9 percent strongly agreed, 48.6 percent agreed) were significant contributors. The study underscores the need for heightened awareness, improved prenatal screening, and tailored interventions to mitigate antepartum hemorrhage risks. Health education on risk reduction strategies and early medical intervention is essential in preventing complications associated with antepartum hemorrhage.